VPN network security with protocols (MMIT Proceedings, 2025)
When using VPN connections, attention is paid to the basic security technologies. Basic VPN protocols Point-to-Point Tunneling Protocol (PPTP), Secure Socket Tunneling Protocol (SSTP), Second-Level Tunneling Protocol (L2TP), OpenVPN, Internet Key Exchange Version 2 (IKEv2), and IPSec are reviewed and analyzed. Attention is also paid to VPN security features.